HUBUNGAN DUKUNGAN KELUARGA TERHADAP MOTIVASI PENGOBATAN PASIEN KANKER: LITERATURE REVIEW - Yone Frillyana; Ika Kurnia; Dini Nur Alpiah (Kampus Akademik Publiser, 2024)
Growth of abnormal cells that tend to attack surrounding tissue and spread to other organs of the body is a non-communicable disease that is a public health problem. In 91 countries from 172 countries around the world, cancer is the first or second most common cause of death before the age of 70 (World Health Organization, 2015). Families of patients undergoing chemotherapy sometimes need support to reduce their despair that their disease cannot be cured or cured. The physical and psychological health effects of chemotherapy can make some patients afraid to receive it. Therefore, families must help cancer patients stay motivated to receive chemotherapy. Research was conducted using the literature review method using the PICO search in the Google Scholar database. Five journals that met the criteria presented the results of the relationship between family support and the motivation to treat cancer patients.